Correlative intercoupling of histomorphometrical values of different heart parts in norm and with chronic heart failure - V. A. Kazakov; S. S. Gutor; I. V. Sukhodolo; V. M. Shipulin; Ye. V. Krivoschyokov (Бюллетень сибирской медицины)
The objective of the given study was to assess statistic dependence of histomorphometrical values of left ventricle (LV) and right atrium (RA) auricle myocardial condition in normal hearts (17 cases) and in hearts with chronic heart failure (CHF) (21 cases). Statistic dependence between morphometrical parameters in LV, RA auricle as well as between these heart parts in both patients without cardiovascular pathology and in patients with CHF was found. In the latter group the amount of correlations decreases in left ventricle and increases between the parts (LV and RA) in comparison with the norm.